Operasi penangkapan dan penanganan hasil tangkapan pole and line KM Sari Usaha 09: Fishing operation and on-board catch handling of KM Sari Usaha 09 pole and liner - Bofmar Sasaleno; Patrice N I Kalangi; Lefrand Manoppo; Alfret Luasuanaung; Heffry V Dien; Fransisco P T Pangalila (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2023)
The utilization of marine biological resources in an effort to increase the production of fishery products has always received serious attention from fishing stakeholders. One of the fishing gear used in exploiting fish resources is pole and line. This study aims to examine pole and line fishing operations and methods of handling the catch on board. This factorrs are important in increasing production with maintained fish quality. This research is descriptive in nature and data collection includes primary data obtained directly from the source or research object, and secondary data obtained indirectly from the research object. Fishing operations include preparation activities, especially ship documents, fishing gear, food supplies, fuel and ice blocks. The operation of pole and line fishing gear uses live bait as a determining factor for fishing success. The types of fish caught are skipjack tuna, yellow fin tuna, dolphinfish, and rainbow runner. The steps taken in the process of handling caught fish on board include preparing catch handling equipment, handling freshly caught fish, and handling fish in holds.